Elizabethan publishing and the makings of literary culture - Melnikoff, Kirk, 1969- (University of Toronto Press, 2018)
Elizabethan Publishing and the Makings of Literary Culture explores the influence of the book trade over English literary culture in the decades following incorporation of the Stationers'Company in 1557. Through an analysis of the often overlooked contributions of bookmen like Thomas Hacket, Richard Smith, and Paul Linley, Kirk Melnikoff tracks the crucial role that bookselling publishers played in transmitting literary texts into print as well as energizing and shaping a new sphere of vernacular literary activity. The volume provides an overview of the full range of practises that publishers performed, including the acquisition of copy and titles, compiling, alteration to texts, reissuing, and specialization. Four case studies together consider links between translation and the travel narrative; bookselling and authorship; re-issuing and the Ovidian narrative poem; and specialization and professional drama. Works considered include Shakespeare's Hamlet, Thévet's The New Found World, Constable's Diana, and Marlowe's Dido, Queen of Carthage. This exciting new book provides both a complement and a counter to recent studies that have turned back to authors and out to buyers and printing houses as makers of vernacular literary culture in the second half of the sixteenth century
Keywords: Englisch ...; Book industries and trade -- England -- History -- 16th century.; Publishers and publishing -- England -- History -- 16th century.; Printing -- England -- History -- 16th century.; Literature publishing -- England -- History -- 16th century.; Transmission of texts -- England -- History -- 16th century.; Literature and society -- England -- History -- 16th century.; Books -- History -- 16th century.; England -- Intellectual life -- 16th century.; Livres -- Industrie -- Angleterre -- Histoire -- 16e siècle.; Édition -- Angleterre -- Histoire -- 16e siècle.; Imprimerie -- Angleterre -- Histoire -- 16e siècle.; Littérature -- Édition -- Angleterre -- Histoire -- 16e siècle.; Transmission de textes -- Angleterre -- Histoire -- 16e siècle.; Littérature et société -- Angleterre -- Histoire -- 16e siècle.; Livres -- Histoire -- 16e siècle.; Angleterre -- Vie intellectuelle -- 16e siècle.; LANGUAGE ARTS & DISCIPLINES -- Journalism.; HISTORY -- Modern -- 16th Century.; Book industries and trade; Books; Intellectual life; Literature and society; Literature publishing; Printing; Publishers and publishing; Transmission of texts; England; Buchhandel; Literatur; 1500-1599; History